Comparative analysis of sexual phase of two species of Microgramma (Polypodiaceae, Pleopeltoideae) - Mendoza-Ruiz, Aniceto; Pérez-García, Blanca (Instituto de Ecología, A.C., 2005)
A comparison was made of the gametophytic development of Microgramma lycopodioides and Microgramma piloselloides. Both species present monolete spores, Vittaria-type germination and Drynaria-type prothallial development. Adult gametophytes are cordate-spatulate to cordate-reniform, with the development of scarce unicellular and pluricellular hairs in the adult stage. The first leaves of the sporophyte are simple and spatulate with polocytic stomata. A comparison was also made and discussed between the prothallic development of both species and that of Microgramma nitida as well as of some species of the genus Pleopeltis, which also present Vittaria-type germination and Drynaria-type prothallial development.